Avaliação do potencial regenerativo das células-tronco derivadas de polpa dentária humana no reimplante dentário tardio: estudo em ratos Wistar - Ventura, Marsha Lisa Schlittler (2014)
Dental replantation success, even in the present day, is limited because much of the teeth is lost due to progressive root resorption, justifying the search for new strategies that can control this problem. Thus, this study aimed to evaluate the regenerative potential of stem cells from human exfoliated deciduous tooth (SHED) in periodontal support after delayed tooth replantation in rats. Forty-five rats (Rattus norvegicus albinus Wistar) had their maxillary right incisor extracted and maintained in dry storage for 60 minutes and then they were replanted into their respective dental socket. The animals were randomly divided into 3 experimental groups with 15 animals each, namely: SHED/PRP group, PRP group and Control group. After this period, the animals were euthanized for histological and histomorphometric analysis. The association between stem cells and platelet-rich plasma, although they didn't have answers to improve the repairing to the level of all tissues that make up the periodontium of insertion, managed to preserve more of the remaining dental. According to our results, the association between stem cells and platelet-rich plasma seems to slow, even if discreetly, the resorption of the dental element. However, the comparative analysis of the data showed no significant statistical difference (p > 0.05) between the study groups in delayed tooth replantation in 15 and 30 days; and in 60 days there was significant statistical difference between the groups for replacement resorption (p < 0.05). These results led to the conclusion that the infusion of stem cells from human exfoliated deciduous tooth (SHED) in the periodontal tissues in the specifications of this study, not favored the process of repair after tooth replantation in rats and that other studies using different parameters, are needed to better assess the effectiveness of stem cells in dental replantation